PENGARUH CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION PADA KONSUMEN ICE CREAM GULU ZHUAN KARAWANG - Karlina; Sudrajat, Ajat (STIE Mahardhika, 2024)
This study examines the influence of customer experience on customer satisfaction at Gulu Zhuan Ice Cream, a brand under the Sour Sally Group known for its Hong Kong Cheese Ice Cream and Sagoo Cream Drinks, specifically focusing on its outlet in Karawang, West Java. The data was collected from 100 respondents who have visited and tasted Gulu Zhuan Karawang Ice Cream through questionnaires. The data analysis was conducted using multiple linear regression tests with the SmartPLS program. The results indicate that customer experience has a significant impact on customer satisfaction when viewed simultaneously. However, out of the five indicators of customer experience, only the